Engineering ethics : contemporary and enduring debates - Johnson, Deborah G., 1945- (Yale University Press, 2020)
An engaging, accessible survey of the ethical issues faced by engineers, designed for students.
Description based upon print version of record.
Keywords: Engineering ethics.; Ingénieurs -- Déontologie.; Technology & Engineering / Social Aspects.; Engineering ethics; Electronic book.